Pre-service EFL Teachers’ Reflective Thinking Skills in Their Instructional Practices - Trisusana, Anis; Arik Susanti; Sueb; Sumarniningsih (English Department, Universitas Negeri Surabaya, 2023)
Reflective skill is a component of 21st century learning and one of the main keys to become a professional teacher. However, pre-service teachers often have difficulty in reflecting their teaching and learning. Thus, this study aims to describe the reflective thinking abilities of pre-service English teachers in implementing their teaching practice. This research was a qualitative descriptive study. The research subjects in this study were 12 pre-service English teachers. The instruments used were observation of documents and interviews. The results indicate that pre-service English teachers tend to practice four reflective thinking skills that are reflection as retrospective analysis (ability to self-assess), reflection as a problem-solving process (awareness of how one learns), critical self-reflection (developing continuous self-improvement), and reflection on self-confidence. The most dominant reflective skill practiced is reflection as a problem-solving process. Meanwhile, testing internal consistency on problem solution become a difficult aspect to be fulfilled by the pre-service teachers. In brief, it is recommended that pre-service teachers should have more opportunity to practice their reflective thinking skills during the teaching and learning process in order to produce professional graduates who have high competitiveness and ability to face the challenges in the world of education.